Is There a Bubble in the German Housing Market? - Konstantin Kholodilin; Claus Michelsen; Dirk Ulbricht (Deutsches Institut für Wirtschaftsforschung (DIW), 2015)
After a period of stagnation that lasted for almost two decades, German house prices began to grow at an accelerated pace since late 2010. Real house prices that even had been declining in 2000-2008 started to climb up steeply from the second half of 2010, followed by a recovery of construction activities. This development raised concerns about the formation of a speculative house price bubble among German policy makers and central bankers. However, empirical evidence of a misalignment of house prices from their fundamentals is mixed.
Keywords: 330